THE OFFENCE-CONSTITUTIONAL CHALLENGES OR CONTROVERSIES. ECONOMIC IMPLICATIONS - Elvira Mihaela PĂTRĂUȘ (Oradea Journal of Business and Economics)
The legal assessment 11 years after the entry into force of the new Criminal Code allows us to argue that the current regulation has posed important challenges for legal theorists and practitioners, with some regulations being declared unconstitutional, others being modified and supplemented to meet the demands imposed by the new realities.